Case Report: Formation of 3D Osteoblast Spheroid Under Magnetic Levitation for Bone Tissue Engineering - Gaitán-Salvatella, Iñigo; López-Villegas, Edgar Oliver; González-Alva, Patricia; Susate-Olmos, Fernando; Álvarez-Pérez, Marco Antonio (Frontiers in Molecular Biosciences, 2021)
Skeletal reconstruction is necessary in cases of bone defects created by tumors, trauma, and abnormalities. Regeneration of bone defects remains a critical problem, and current approaches are based on biocompatible scaffolds. Spheroids represent a simple 3D system since no supporting material is required for cell growth. Different techniques are used to generate spheroids, such as hanging drop, low-attachment plates, and magnetic nanoparticles. The idea of using magnetic nanoparticles is to cross-link through cell membrane overnight to create complex 3D cellular spheroid by using magnets to guide the cellular response. Herein, the current study aimed to achieve 3D human fetal osteoblast (hFOB) spheroid under magnetic levitation. Formation of 3D spheroid culture under magnetic levitation was evaluated by cell viability at 3, 7, and 14 days. Morphology of the 3D hFOB spheroid was analyzed by SEM and fluorescence microscopy and the differentiation towards mineralized lineage by ALP assay, qPCR, and alizarin red staining. The cell viability indicated that the 3D hFOB spheroid still viable after 14 days of culture. ALP assay, qPCR analysis expression of Col1, ALP, and Itg-β1 molecules, and calcium deposition with alizarin red showed a high level of bioactivity of the 3D hFOB spheroid. SEM images allowed the morphological analysis of the 3D microtissue-like spheroid with the presence of matrix deposition. These results indicate that magnetic levitation culture enables 3D stable osteoblast spheroids and could be a promising strategy for engineering application in the 3D construct in surgery regeneration of mineralized tissue.